Evaluation of the impact of postural restrictions after Semont liberatory maneuver on immediate reactions and short-term outcome in the posterior semicircular canal canalolithiasis: a preliminary study - Andrea Albera; Marco Boldreghini; Sergio Lucisano; Roberto Albera; Claudia Cassandro; Alma Barci; Giuseppe Riva; Andrea Canale (Frontiers in Neurology)
IntroductionBenign paroxysmal positional vertigo is the most frequent peripheral vestibular disorder, characterized by brief but intense vertigo crises related to changes in position. The Liberatory maneuver is considered the gold-standard treatment, with a short-term resolution of the vertigo in over 70% of cases, and achieving a 90% success rate after four maneuvers. An immediate reaction to the subsequent repositioning maneuver is often an orthotropic nystagmus (Ny) occurring in the same direction as the Ny observed after returning to the primary position. This reaction, occurring seconds to minutes after reaching the second position, is considered a positive predictor of the maneuver’s effectiveness. To improve the success rate after the maneuver, many authors have suggested postural restrictions.MethodsTo determine the best predictors of outcome between the immediate behavior after the Semont maneuver and postural restriction, we analyzed 102 patients with posterior semicircular canalithiasis who underwent the Semont maneuver. In each case, we assessed the immediate reaction to the maneuver. Postural restrictions were recommended to 55 participants, while the remaining 40 were instructed to engage in normal head movements, even immediately following the maneuver.ResultsThe resolution rate was almost the same (69% versus 62%), regardless of postural behavior, while a significantly high success rate was obtained in the presence of Ny in position 2 of the Semont maneuver.ConclusionOur results support the hypothesis that postural restriction is not necessary after the Semont maneuver and that the occurrence of Ny during position 2 is the main outcome indicator.